Memo from John Leonard to Walter Donner - Leonard, John E. (1958)
The memo discusses a study of Zeromatic pH meters and includes a handwritten table of data. Arnold Beckman invented his first pH meter in 1934 at the request of a chemist from the California citrus industry, who needed an accurate way to measure the acidity of his product. The resulting instrument kicked off rapid development not only of Beckman Instruments, Inc. but also of the electronic scientific instrument industry.
Keywords: Scientific apparatus and instruments; Hydrogen-ion concentration--Measurement; Hydrogen-ion concentration; Beckman Instruments, Inc.